Matrix converter open circuit fault behavior analysis and diagnosis with a model predictive control strategy - Zhang, Jiawei; Dan, Hanbing; Empringham, Lee; De Lillo, Liliana; Wheeler, Patrick (IEEE, 2018)
A novel fast and reliable open circuit fault diagnosis strategy for a Matrix Converter with a Finite Control Set Model Predictive Control strategy is proposed in this paper. Current sensors are located ahead of the clamp circuit to measure the output currents in order to improve the speed of fault diagnosis. In addition, the current recirculating path during a single open circuit switch fault condition is given in detail with the aim of contributing more expert knowledge to the fault diagnosis. The proposed fault diagnosis method is applicable over the whole range of modulation index.